CCR2-mediated antiinflammatory effects of endothelial tetrahydrobiopterin inhibit vascular injury-induced accelerated atherosclerosis. - Ali, Z; Bursill, C; Douglas, G; McNeill, E; Papaspyridonos, M; Tatham, A; Bendall, J; Akhtar, A; Alp, N; Greaves, D; Channon, K (2008)
BACKGROUND: Vascular injury results in loss of endothelial nitric oxide (NO), production of reactive oxygen species (ROS), and the initiation of an inflammatory response. Both NO and ROS modulate inflammation through redox-sensitive pathways. Tetrahydrobiopterin (BH4) is an essential cofactor for endothelial nitric oxide synthase (eNOS) that regulates enzymatic synthesis of either nitric oxide or ROS. We hypothesized that endothelial BH4 is an important regulator of inflammation and vascular remodeling. METHODS AND RESULTS: Endothelium-targeted overexpression of GTP cyclohydrolase 1 (GCH), the rate limiting enzyme in BH4 synthesis, increased levels of tetrahydrobiopterin (BH4), reduced endothelial superoxide, improved eNOS coupling, and reduced vein graft atherosclerosis in transgenic GCH/ApoE-KO mice compared to ApoE-KO controls. Immunohistochemistry using anti-MAC-3 and MAC-1 antibody staining revealed a marked reduction in vein graft macrophage content, as did RT-PCR expression of macrophage marker CD68 mRNA levels in GCH/ApoE-KO mice. When we investigated the potential mediators of this reduction, we discovered that mRNA and protein levels of MCP-1 (CCL2) but not RANTES (CCL5) were significantly reduced in GCH/ApoE-KO aortic tissue. Consistent with this finding we found a decrease in CCR2-mediated, but not CCR5-mediated, chemotaxis in vascular tissue and plasma samples from GCH/ApoE-KO animals. CONCLUSIONS: Increased endothelial BH4 reduces vein graft neointimal hyperplasia and atherosclerosis through a reduction in vascular inflammation. These findings highlight the importance of MCP-1/CCR2 signaling in the response to vascular injury and identify novel pathways linking endothelial BH4 to inflammation and vascular remodeling.